The Development of Mental Capacity in Preschool Children with regard to the Theory of Mind - Ferman Hasan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
This research attempted to investigate the growth and development of mental abilities in pre-school children from the viewpoint of the theory of mind. The aim of the study is to find out the nature of mental development and mental abilities of pre-school children. This research is based on the descriptive and qualitative approach and the method of content analysis to review and compare four research studies related to the relationship of mental abilities development in preschool children in terms of theory of mind. The results of this research indicate the emergence of mental abilities and theory of mind in the preschool period according to three stages, the first stage (0-1) years, the second stage (3-5) years, and the third stage (5-6) years , in some way in each of the three stages there is a clear growth and development of mental abilities which helps to manifest the theory of mind. This study refers to the emergence of mental abilities before the age of six and the impact of school and the school environment in achieving and embodying the theory of mind at that stage.